Dual Planar‐Helix Type Energy Storage Wires to Circumvent Universal Energy Lag Effect. Issue 4 (3rd December 2015) - Nam, Inho; Park, Jongseok; Park, Soomin; Bae, Seongjun; Yoo, Young Geun; Yi, Jongheop
Abstract : There has been an unsolvable bottleneck in energy storage wires, with greatly diminished energy even when the most advanced materials are used. Here, the bottleneck is proved using analytical derivation, which is referred as an "energy lag effect." To solve the effect, a new‐type energy storage wires are designed, including a dual planar‐helix structure. The systems do not show any energy lagging, experimentally or analytically.